2021
DOI: 10.1063/5.0050474
|View full text |Cite
|
Sign up to set email alerts
|

Extended aging of Ge–Se glasses below the glass transition temperature

Abstract: Germanium selenide glasses of compositions spanning the whole glass-formation range are aged at room temperature for up to twenty years. A prominent enthalpy relaxation process is observed in all glasses and its structural origin is analyzed by Raman spectroscopy. The structural relaxation is manifested in the Raman spectra as a decrease in the ratio of edge to corner-sharing GeSe 4/2 tetrahedral units. This structural evolution can be explained in terms of configurational entropy and density changes. Changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 66 publications
(104 reference statements)
0
6
0
Order By: Relevance
“…The higher the fragility, the more structural relaxation the system will experience while in the glassy state (RESET state). [ 59 ] This is detrimental as pronounced relaxation processes lead to pronounced aging effects like density increase and resistivity drift. [ 14 ] Small temperature changes also lead to a large change in relaxation time in fragile systems, thereby leading to the potential instability of the glassy memory cell upon temperature variations.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the fragility, the more structural relaxation the system will experience while in the glassy state (RESET state). [ 59 ] This is detrimental as pronounced relaxation processes lead to pronounced aging effects like density increase and resistivity drift. [ 14 ] Small temperature changes also lead to a large change in relaxation time in fragile systems, thereby leading to the potential instability of the glassy memory cell upon temperature variations.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, spectroscopic studies on As 30 Se 70 glass have indicated that prolonged (20 years) aging at ambient temperature results in a net conversion of two As–Se–Se–As linkages into one As–Se–As and another As–Se–Se–Se–As linkage . In the case of the Ge–Se system, previous Raman spectroscopic studies have shown that the most prominent aging-induced T f -dependent structural change in glasses with excess Se (70–90% Se) involves the conversion of the edge-shared GeSe 4 tetrahedra into corner-shared tetrahedra. , The timescale of this conversion process was shown to be consistent with that of enthalpy relaxation and to be an important source of S conf in supercooled Ge 20 Se 80 liquid near the glass transition range. Similarly, T f -dependent tetrahedral speciation was reported in a recent Raman spectroscopic study to be responsible for the structural relaxation of Si 25 Se 75 glass during aging at 40 K below T g .…”
Section: Introductionmentioning
confidence: 99%
“…34,35 In region II, new bands at 140, 169 and 195 cm −1 are observed, mainly characteristic of AsTe (3/2) , Se–Te and GeSe tetrahedral structures. 16,36,37 At higher concentrations of As 2 Se 3 , Raman bands at 167, 194 and 229 cm −1 are observed and are characteristic of As–Se based vibrational units. 38 These observations indicate the influence of As 2 Se 3 on modulating the structural network of (GeTe 4 ) 100− x (As 2 Se 3 ) x glasses.…”
Section: Resultsmentioning
confidence: 96%
“…discussed that the compositions outside and inside the IP window show significant relaxation with time. 16…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation